POTENSI DAN DAYA DUKUNG KAWASAN EKOWISATA HUTAN MANGROVE BANDAR BAKAU DUMAI - Rizky Budi Susanto; Defri Yoza; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Tourism is a potential sector that being developed in the city of Dumai. Mangrove forest Bandar Bakau Dumai has a potential to be developed into ecotourism because it has a rich flora and fauna diversity that characterized by many of visitors in these area. Many of visitors in these area fearful could damage the mangrove forest. The aim of these research were to determine the potential of flora mangrove and fauna diversity that can be developed as an ecotourism attraction and analyze the carrying capacity in ecotourism track of mangrove forest Bandar Bakau Dumai. These research was conducted in ecotourism track of mangrove forest Bandar Bakau Dumai used survey method, study literature and interview. The results of these research showed that potential in the form of 14 mangrove species of flora and fauna in the form of 7 species of animals that includes high potential for the development of ecotourism with that value of the carrying capacity was 149 visitors/day.Keywords: Ecotourism, Potential, Flora, Fauna, Carrying Capacity, Mangrove Forest, Bandar Bakau Dumai